Strategic and operational remanufacturing mental models: a study on Chinese automotive consumers buying choice - Moosmayer, Dirk; Abdulrahman, Muhammad; Subramanian, Nachiappan; Bergkvist, Lars (Emerald Publishing, 2019)
Purpose: Remanufacturing is the only end-of-life (EOL) treatment process that results in as-new functional and aesthetic quality and warranty. However, applying mental model theory, we argue that the conception of remanufacturing as an EOL process activates an operational mental model(OMM) that connects to resource reuse, environmental concern and cost savings and is thus opposed to a strategic mental model (SMM) that associates remanufacturing with quality improvements and potential price increases. Design/methodology/approach: We support our argument by empirically assessing consumers’multi-attribute decision process for cars with remanufactured or new engines among 202 car buyers in China. We conduct a conjoint analysis and use the results as input to simulate market shares for various markets on which these cars compete. Findings: The results suggest that consumers on average attribute reduced utility to remanufactured engines, thus in line with the OMM. However, we identify a segment accounting for about 30 % of the market with preference for remanufactured engines. The fact that this segment has reduced environmental concern supports the SMM idea that remanufactured products can be bought for their quality. Research limitations/implications: A single-country (China) single-brand (Volkswagen) study is used to support the conceptualised mental models. While this strengthens the internal validity of the results, future research could improve the external validity by using more representative sampling in a wider array of empirical contexts. Moreover, future work could test our theory more explicitly. Practical implications: By selling cars with remanufactured engines to customers with a strategic mental model that values the at least equal performance of remanufactured products, firms can enhance their profit from remanufactured products. In addition, promoting SMM enables sustainable business models for the sharing economy. Originality/value: As a community, we need to more effectively reflect on shaping mental models that disconnect remanufacturing from analogies that convey inferior quality and performance associations. Firms can overcome reduced utility perceptions not only by providing discounts, i.e. sharing the economic benefits of remanufacturing, but even more by increasing the warranty, thus sharing remanufacturing’s performance benefit and reducing consumers’ risk, a mechanism widely acknowledged in product diffusion but neglected in remanufacturing so far.